2017
DOI: 10.1093/mnras/stx1846
|View full text |Cite
|
Sign up to set email alerts
|

High-energy gamma-rays from Cyg X-1

Abstract: We have obtained a firm detection of Cyg X-1 during its hard and intermediate spectral states in the energy range of 40 MeV-60 GeV based on observations by the Fermi Large Area Telescope, confirming the independent results at ≥60MeV of a previous work. The detection significance is 8σ in the 0.1-10 GeV range. In the soft state, we have found only upper limits on the emission at energies 0.1 MeV. However, we have found emission with a very soft spectrum in the 40-80 MeV range, not detected previously. This is l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 50 publications
4
74
0
1
Order By: Relevance
“…Corbel et al 2012;Zdziarski et al 2018) and Cygnus X-1 (e.g. Bodaghee et al 2013;Zanin et al 2016;Zdziarski et al 2017).…”
Section: Introductionunclassified
“…Corbel et al 2012;Zdziarski et al 2018) and Cygnus X-1 (e.g. Bodaghee et al 2013;Zanin et al 2016;Zdziarski et al 2017).…”
Section: Introductionunclassified
“…The high proximity to the star also makes IC emission and GGA more susceptible to change along the orbit, which results in a much stronger orbital modulation than in MB18, especially for high-energy gamma rays with ε 100 MeV. Evidence of such a modulation has been found for Cygnus X-3 (Zdziarski et al 2018), and hints of such an effect have also been observed in Cygnus X-1 (Zanin et al 2016;Zdziarski et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 97%
“…Cyg X-1 and Cyg X-3 are both detected in the lower gamma-ray energies by the Fermi satellite and the origin of this emission seems to be the jet (Abdo et al 2009, Zanin et al 2016, Zdziarski et al 2016. Therefore, it is to be expected that during flares the emission would extend also to energies > 100 GeV, unless the gamma-rays are always emitted very close to jet base, where strong photon field absorbing VHE γ-rays is present.…”
Section: Supermassive Black Hole In the Centre Of Our Galaxymentioning
confidence: 99%